Efeito agudo do exercício aeróbio em diferentes intensidades no transporte mucociliar de pacientes com DPOC - Leite, Marceli R. [UNESP]; Ramos, Ercy Mara C. [UNESP]; Freire, Ana Paula C.F. [UNESP]; De Alencar Silva, Bruna S. [UNESP]; Nicolino, Juliana [UNESP]; De Toledo, Alessandra C.; Vanderlei, Luiz Carlos M. [UNESP]; Ramos, Dionei [UNESP] (My University, 2015)
Design of the Study: Clinical Trial. Objective (s): To analyze the acute effect of aerobic exercise at different intensities in mucociliary clearance in patients with COPD, and to investigate possible associations of the autonomic nervous system in this response. Methods: 22 COPD patients underwent an initial evaluation for collecting personal data and spirometry to assess lung function. It was performed a progressive treadmill test for aerobic exercise prescription. Finally two randomized sessions of aerobic exercise with intensity of 60 % and 90 % of peak speed reached during the incremental test (vVO2peack) were performed with at least 24 hours of rest between them. The mucociliary clerance was assessed before and after the exercise sessions by testing the saccharin transit time (STT). Assessment of autonomic modulation was performed by heart rate variability (HRV) which continued throughout the protocol. Results: The values obtained in the STT test after aerobic exercise at 60 % of vVO2peack (9,08 minutes ± 4,96) was lower when compared to the STT before exercise (11,96 ± 6,31, p = 0,005). That response also occurred after aerobic exercise at 90% of vVO2peack (8,90 ± 4,21 min) compared to baseline (12,94 ± 7,22, p = 0,023). Correlation analysis between the final values of STT test and HRV indexes did not show significant differences. Conclusions: Patients with COPD showed acceleration of mucociliary clerance right after a session of aerobic exercise. It was not possible to observe the association of autonomic modulation in this response.
Acute effect of aerobic exercise in different intensities in mucociliary clearance of patients with COPD
Keywords: Aerobic treatment; Chronic obstructive; Exercise therapy; Mucociliary clearance; Pulmonary disease